Rural livelihood diversity and its influence on the ecological intensification potential of smallholder farms in Kenya. (22nd October 2020) - Kansiime, Monica K.; Girling, Robbie D.; Mugambi, Idah; Mulema, Joseph; Oduor, George; Chacha, Duncan; Ouvrard, David; Kinuthia, Wanja; Garratt, Michael P. D.
Abstract: Smallholder farmers represent the majority of food producers around the world, yet they are often the most at risk of suffering yield gaps and not achieving their production potential. Ecological Intensification (EI) is a knowledge intensive approach to sustainable agricultural intensification which utilizes biodiversity‐based ecosystem services to support greater yield and reduce reliance on agrochemical inputs. Despite the potential benefit of EI based practices, uptake by smallholders is not as widespread as it could be. Here we test the hypothesis that application of EI on smallholder farms in Kenya is a viable approach that could be taken in order to enhance food security. Focusing on natural pest control and crop pollination, we used farmer surveys to explore the potential for EI in central Kenya. We identified to what extent farm typology and access to knowledge determine the incentives and barriers facing smallholder producers and how this influences optimal pathways for sharing knowledge and providing extension services. We found considerable potential for EI of smallholder farms in this region; most farmers grew insect pollinated crops and some farmers already employed EI practices, while others relied heavily on chemical pesticides. Based on physical, social, and economic factors, three farm typologies emerged including "semi‐commercial, " "market orientated, " and "subsistence." These typologies influenced the appropriate EI practices available to farmers, as well as routes through which knowledge was shared, and the extent to which extension services were utilized. We propose that to support effective uptake of EI practices, smallholder farm heterogeneity should be acknowledged and characterized in order to target the needs and capabilities of farmers and identify appropriate knowledge sharing and support pathways. The approach we take here has the potential to be employed in other regions globally. Abstract : Ecological intensification has the potential to improve food security in smallholder farms in Kenya. However, smallholder farms vary considerably based on socioeconomic factors, and farm typologies influenced the appropriate EI practices available to farmers, as well as routes through which extension support can be provided. To support widespread uptake of EI practices, smallholder farm heterogeneity should be acknowledged and characterized in order to target the needs and capabilities of farmers and identify appropriate knowledge sharing and support pathways.